2019
DOI: 10.1111/1346-8138.14992
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intralesional injection of lauromacrogol combined with triamcinolone for infantile hemangiomas

Abstract: The efficacy of lauromacrogol injection therapy and intralesional triamcinolone for infantile hemangiomas (IH) has been well documented recently, but with an increase in serious or rare adverse reactions. The aim of this study is to investigate the safety concerns regarding intralesional injection of lauromacrogol combined with triamcinolone for IH and to study its effect on infant growth and development. A total of 1039 IH patients who were subjected to intralesional injection of lauromacrogol combined with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The chemical composition of lauromacrogol produced in China is the same as that of polidocanol and has been approved for clinical use since 2008. A retrospective study showed that an intralesional injection of lauromacrogol combined with triamcinolone under general anesthesia was safe and effective as a treatment for IH 15 . This study retrospectively evaluated the long‐term appearance of IH treated with the intralesional stratified injection of gradient‐diluted lauromacrogol alone under surface anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of lauromacrogol produced in China is the same as that of polidocanol and has been approved for clinical use since 2008. A retrospective study showed that an intralesional injection of lauromacrogol combined with triamcinolone under general anesthesia was safe and effective as a treatment for IH 15 . This study retrospectively evaluated the long‐term appearance of IH treated with the intralesional stratified injection of gradient‐diluted lauromacrogol alone under surface anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is generally regarded as the last resort ( 18 ). There have been dermatological reports on the usefulness and tolerability of direct injection of polidocanol for the treatment of cutaneous hemangiomas ( 19 , 20 ). Despite limited information being available on the efficacy of endoscopic sclerotherapy for small bowel lesions, our case demonstrated that the treatment successfully reduced the size of the ileal hemangioma by >50% in comparison to the pretreatment size ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate for side effects, based on 48 studies and 3,352 patients, was 7.1% (12, 34-67, 70-72, 74-77, 79, 80, 83-87). Six studies mentioned the need for additional treatment (local or systemic) for adverse events (38,40,45,52,54,69). The aggregated mean and median follow-up lengths were 17.09 and 12 months, respectively.…”
Section: Patients Characteristics and Therapeutic Approachmentioning
confidence: 99%